"No somos negros" - Lepe Carrión, Patricio (Nómadas. Critical Journal of Social and Juridical Science, 2010)
It attempts to show the displacement of pejorative meanings imposed dominant discourses on culture, so to sustain a racial difference that justifies the marginalization and exploitation of minorities. To do this, be taken as metaphoric and metonymic figure the old Castilian expression ’No Somos Negros’ (‘We’re not Black’). From there, we will produce a work of deconstruction of the concept of ’blackness’ to see how this concept entails the displacement of a number of meanings discriminatory. We conclude that the denial of our blackness, is the assertion of racial difference inherited from colonial times until today.